Killer bees! - Waring, Rob; Heinle Cengage Learning (London : Heinle, Cengage Learning/National Geographic, 2008)
The native bees of Central America are important for farmers, the rain forests and food production. However, a new kind of'killer bee' is moving in and taking over the rain forests. What will happend to the native bees? Can the killer bees be stopped?
Title from title screen
Video and audio on DVD
Pre-intermediate 1000 headwords
DVD format
Optional audio and subtitle in American English or British English
Keywords: Geography